2003
DOI: 10.1093/pubmed/fdg025
|View full text |Cite
|
Sign up to set email alerts
|

Social class, ethnicity and attendance for antenatal care in the United Kingdom: a systematic review

Abstract: There is little good quality evidence on social and ethnic inequalities in attendance for antenatal care in the United Kingdom. Recommendations for further research are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
1
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 21 publications
5
86
1
9
Order By: Relevance
“…Although there has been little meticulous evaluation of optimal timing of the initiation of ANC, pregnant women who receive late or no ANC are more likely to have poor or unfavorable outcomes of pregnancy. [4][5][6] Late initiation of ANC was reported as a significant risk factor for maternal mortality in some studies. [7][8][9] Therefore, ANC should begin as early as possible either at hospital/health center or during domiciliary visit of health workers in order to have sufficient time to manage risk factors, if present or to perform appropriate screening for early and timely referral.…”
Section: Introductionmentioning
confidence: 99%
“…Although there has been little meticulous evaluation of optimal timing of the initiation of ANC, pregnant women who receive late or no ANC are more likely to have poor or unfavorable outcomes of pregnancy. [4][5][6] Late initiation of ANC was reported as a significant risk factor for maternal mortality in some studies. [7][8][9] Therefore, ANC should begin as early as possible either at hospital/health center or during domiciliary visit of health workers in order to have sufficient time to manage risk factors, if present or to perform appropriate screening for early and timely referral.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have suggested that the quality of prenatal care is poorer among pregnant women who are single, adolescent, have a higher number of children, low schooling, lower income, and belong to ethnic minorities. 7,18 Care fragmentation, that is, medical consultations performed by different professionals, has also been associated with low quality of prenatal care. 14 The pregnant woman's psychosocial aspects are little approached in the investigation of the determinants in prenatal care.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the delay between pregnancy confirmation in primary care and the first midwifery appointment is greater for women from minority ethnic groups than for other women, [14][15][16] Although there was some evidence that women from some minority ethnic groups attend primary care to confirm their pregnancies approximately 1 week later than other women, there was no evidence that the 7-week delay between pregnancy confirmation and testing was associated with ethnic group. This indicates that delays within the health service, rather than women reporting late to confirm their pregnancies, are responsible for the large observed delay in testing.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%